PENGARUH KUALITAS PENCATATAN DAN PELAPORAN TERHADAP TATA KELOLA ADMINISTRASI DI WILAYAH KERJA PUSKESMAS SIBOLANGIT TAHUN 2017 - Tampubolon, Elmina; Sitorus, Friska; Efriza, Efriza (Jurnal Inovasi Kesehatan Masyarakat, 2019)
Regristration and reporting system of Public Health Center is vital instrument in health system. The information about the pain, the use of health service at Public Health Center, death and many others health information is beneficial to have decision and policy maker at Regency stage, city and Sub-regency. This research aims to analyze the influence quality of registration and reporting toward administrative system at Pubilic Health Center of Sibolangit in 2017. This research is explanatory research with cross sectional as discover, analyze and explain how the influences quality or registration and reporting toward administrative system at Pubilic Health Center of Sibolangit in 2017. The sample of this research is all populations (random sampling) who are the staff who work in Public Health Center of Sibolangit as many as 50 people. The result of input factors found that budgeting in registration and reporting is good (82%), capacity resource support (86%), mainstay variable in handling good registration and reporting (74%), good respond (76%). The factor of process, data respondents collecting who said good (68%), good sending process of respondents data (52%), bad sending process (48%). From data analysis found that respondents who said good (65%). Output factors, good planning variable (36%), with good evaluation (58%), punctuality to handle and make good report (60%), safety of saving data file (52%). The bivariat result show that there is significant influences between collecting data, sending data, analysis data, planning, punctuality, completencess with implematation of administration system at Public Health Center of Sibolangit. There is no significant influences between budgeting, capacity resources, mainstay, respond capacity, and evaluation with administrative system at Pubilc Health Center of Sibolangit. The result of multivariate analysis found that dominant factors is collecting data with value 1,637. For health department needs the efforts comprehensive ordering on organizing of Registration and reporting system of Public Health Center to progress and application of health information system at Public Health Center.